Monitoring Enables Progress: A Nationwide Quality Improvement Program in Children With Crohn Disease. Issue 2 (August 2021) - Yogev, Dotan; Shosberger, Adi; Nehemia, Chen; Harel, Sasha; Yerushalmy-Feler, Anat; Ledder, Oren; Orlanski-Meyer, Esther; Assa, Amit; Slae, Mordechai; Kori, Michal; Elenberg, Yigal; Shaoul, Ron; et al.
ABSTRACT: Objectives: In this quality improvement program, named quality in pediatric inflammatory bowel disease, we constructed a nation-wide platform that prospectively recorded clinically important quality indicators in pediatric inflammatory bowel diseases (PIBD), aiming at improving clinical management across the country. Methods: Representatives of all 21 PIBD facilities in Israel formed a Delphi group to select quality indicators (process and outcomes), recorded prospectively over 2 years in children with Crohn's disease 2–18 years of age seen in the outpatient clinics. Monthly anonymized reports were distributed to all centers, allowing comparison and improvement. Trends were analyzed using the Mann-Kendall test, reporting τ (tau) values. Results: The indicators of 3254 visits from 1709 patients were recorded from September 2017 to September 2019 (mean age 14.7 ± 3.1 years, median disease duration 1.8 years (interquartile range 0.69–4.02)). An increase in three of five process indicators was demonstrated: obtaining drug levels of anti-tumor necrosis factor (TNF) (τ = 0.4; P  = 0.005), utilization of fecal calprotectin (τ = 0.38; P  = 0.008) and bone density testing (τ = 0.45; P  = 0.002). Among outcome indicators, three of nine improved as measured during the preceding year: calprotectin <300 μg/mg (τ = 0.35; P  = 0.015), and "resolution of inflammation" defined as a composite of endoscopy, imaging and fecal calprotectin (τ = 0.39; P  = 0.007). Endoscopic healing reached borderline significance (τ = 0.28; P  = 0.055). An increase in the use of biologics throughout the study was observed (τ = 0.47; P  = 0.001) with a concurrent decrease in the use of immunomodulators (τ = −0.47; P  = 0.001). Conclusions: Quality improvement nationwide programs can be implemented with limited resources while facilitating standardization of care, and may be associated with improvements in measured indicators. Abstract : Supplemental Digital Content is available in the text